Selva central : history, economy, and land use in Peruvian Amazonia - Santos-Granero, Fernando, (Smithsonian Institution Press)
"Carefully researched and written history of the Peruvian Amazon region emphasizes early settlement patterns, land use, missionary work, and various crops. Particular attention is paid to coffee, fruit crops, and timber in this regional economy. Eschews the political aspects of border disputes or border locations that have historically troubled this region. Highly recommended as a study with a primary emphasis for geographers"--Handbook of Latin American Studies, v. 58.